2014
DOI: 10.3758/s13415-014-0330-7
|View full text |Cite
|
Sign up to set email alerts
|

Lexical enhancement during prime–target integration: ERP evidence from matched-case identity priming

Abstract: A number of experiments have revealed that matched-case identity PRIME-TARGET pairs are responded to faster than mismatched-case identity prime-TARGET pairs for pseudowords (e.g., JUDPE-JUDPE < judpe-JUDPE), but not for words (JUDGE-JUDGE = judge-JUDGE). These findings suggest that prime-target integration processes are enhanced when the stimuli tap onto lexical representations, overriding physical differences between the stimuli (e.g., case). To track the time course of this phenomenon, we conducted an event-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 51 publications
(77 reference statements)
6
56
1
Order By: Relevance
“…(), who found that for pseudo‐words, but not for words, matched‐case identity PRIME–TARGET pairs were responded to faster than mismatched‐case identity prime–TARGET pairs. A similar finding was also reported by Vergara‐Martínez, Gómez, Jiménez, and Perea (). The explanation of these case‐specific identity priming effects for pseudo‐words and pseudo‐brands is not entirely clear, but presumably reflects non‐lexical processing (we return to this issue in the General Discussion).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(), who found that for pseudo‐words, but not for words, matched‐case identity PRIME–TARGET pairs were responded to faster than mismatched‐case identity prime–TARGET pairs. A similar finding was also reported by Vergara‐Martínez, Gómez, Jiménez, and Perea (). The explanation of these case‐specific identity priming effects for pseudo‐words and pseudo‐brands is not entirely clear, but presumably reflects non‐lexical processing (we return to this issue in the General Discussion).…”
Section: Discussionsupporting
confidence: 90%
“…() and Vergara‐Martínez et al . (). One possible explanation for the interaction of Prime Type and Target Case for pseudo‐brands is that it could reflect differences in the evidence accumulation process.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, in a masked priming experiment, Jacobs et al (1995) found that the lowercase prime judge and the uppercase prime JUDGE were equally effective at activating the target word JUDGE (i.e., there was no advantage of the physically identical condition over the nominally identical condition). In an electrophysiological experiment, Vergara-Martínez et al (2015) replicated this behavioral phenomenon and found a difference between judge - JUDGE and JUDGE - JUDGE in an early (visual) ERP component (N/P150)—this difference completely disappeared in orthographical-lexical components (N250 and N400). Similarly, Bowers et al (1998) found an equivalent magnitude of masked identity priming, relative to an unrelated condition, for words that look visually similar across case (e.g., kiss - KISS ) and for cross-case words that look visually dissimilar across case (e.g., gale - GALE ).…”
Section: Introductionmentioning
confidence: 89%
“…It appears that capacity benefits because of lexicality expressed in RT distributions can't accumulate unless a continuation of form constraint at the level of stroke-units is met. Importantly, the differences across the terminals-deleted, midsegments-deleted and junctions-deleted conditions -highlighted above -did not appear for nonword stimuli, which suggests either that top-down processes from lexical levels may be at play here (e.g., see Perea, Jiménez, & Gomez, 2014;Perea, Marcet, & Vergara-Martínez, 2016;Vergara-Martínez, Gomez, Jiménez, & Perea, 2015), or that already well before 60 ms after stimulus onset (cf. van Leeuwen, 2015) the activity of early neurons in visual cortex may become dependent on that of their neighbours through within-layer horizontal connections for familiar words.…”
Section: Resultsmentioning
confidence: 92%